HOW CAPITALISM AND RACISM CONTINUE TO SHAPE THE SOCIO-ECONOMIC STRUCTURE OF SOUTH AFRICA - Makgetlaneng, Sehlare (Africanus: Journal of Development Studies, 2016)
This work provides a critical analysis of the dialectical and organic relationship between the benefits and misfortunes of capitalism and racism as an integral socio-economic part of the South African history since the inception of capitalism and racism in the country in the 15th century. This task is executed by highlighting the importance of the dialectical and organic relationship between race and class. It maintains that the primacy of class over race in terms of importance has existed since the inception of capitalism and racism. The theoretical and practical recognition of the primacy of class over race in terms of importance in the South African political economy is of strategic importance in the struggle for structural socio-economic change and transformation in the country. This struggle constitutes the efforts to solve the structural problem of the benefits of capitalism and racism enjoyed by the decisive minority of its population and their misfortunes confronted or encountered by the decisive majority in the past and present tenses of its history. It maintains that to best and effectively serve the needs and demands of the struggle for structural social change and transformation, whose aim is to end the benefits and misfortunes of capitalism and racism, it is of strategic and tactical importance to dialectically and organically weave the relationship between race and class without departing from the importance of the racial factor in the South African political economy.